Do Adaptability and Innovation Speed Matter in Increasing Sales of MSMEs during the COVID-19 Pandemic? - Rahmat Sabuhari; Marwan Man Soleman; Mukhtar A. Adam; Sulfi Abdul Haji (Universitas Hayam Wuruk Perbanas, 2023)
Micro, Small, and Medium-sized Enterprises (MSMEs) in Eastern Indonesia are threatened with bankruptcy during the COVID-19 pandemic. This situation occurred due to significantly decreased peopleâ€™s purchasing power, and most production activities stopped. In light of this issue, this study aims to investigate how well MSMEsâ€™ adaptability and innovation speed in Eastern Indonesia have increased their sales during the pandemic. We collected the data by distributing questionnaires on offline and online channels using Google Forms to MSMEs owners in Maluku and North Maluku Provinces. We eventually gathered 262 pieces of data and analyzed it through the PLS-SEM approach. The results showed that adaptability has a positive and significant effect on sales and the speed of innovation, while innovative speed has no impact on sales. In other words, the innovation speed can also not mediate adaptability to MSMEs sales. The results of this study are expected to benefit MSMEs owners in implementing appropriate business strategies, especially how MSMEs owners have the adaptability and innovation speed to manage their business in this condition of uncertainty. Additionally, this research is expected to provide an empirical contribution to the government of Indonesia in making considerations, policies, and decision-making related to the empowerment of MSMEs during the pandemic and beyond.Â